Drug-induced liver injury after covid-19 mRNA vaccine: case report (Colombia Medica, 2022)
Case description:A 22-year-old female patient received the first dose of Pfizer-BioNTech vaccine (RNAm) against COVID-19; 6 days later, she presented abdominal pain located in the right hypochondrium and epigastrium, associated with emetic episodes. Consultation 21 days later due to the same symptoms; three days after the seconddose of the vaccine was administered. Clinical findings:Pain on palpation in the right hypochondrium. Laboratories reported hepatocellular lesions and cholestasis, with negative amylase, hepatotropic virus and autoimmune hepatitis tests. Liver and biliary tract ultrasound and cholangioresonance were normal.Treatment and Results:Hyoscine and intravenous fluids as support therapy. She presented improvement in abdominal pain and a progressive decrease of transaminases and bilirubin levels until normalization and was discharged on the fifth day of hospitalization. A drug-associated hepatotoxicity (DILI) diagnosis was considered probable, in this case, secondary to vaccination against COVID-19. Clinical Relevance:The current SARS-CoV-2 pandemic has spurred the development of new vaccines, the safety of which remains a concern. There is a likely causal relationship between vaccination and liver involvement in this clinical case rather than simply a sporadic occurrence.